1991
DOI: 10.1002/ijc.2910470510
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of proliferative activity in carcinomas of the human alimentary tract by Ki‐67 immunostaining

Abstract: The monoclonal antibody (MAb) Ki-67, which is directed against a proliferation-associated nuclear antigen, was used to measure tumor proliferation in 165 carcinomas of the esophagus, stomach, colon and rectum with an indirect immunoperoxidase technique. The percentage of Ki-67-positive tumor cells (Ki-67 index) was evaluated with the point-counting method. The Ki-67 index in gastric cancers (mean, 24.8%; standard deviation, 11.1%) was significantly lower than in tumors of the esophagus (35.7 +/- 12.6%), colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
22
3
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 28 publications
8
22
3
1
Order By: Relevance
“…The MIB-1 indices obtained in our study are in line with the results of earlier studies that had used the Ki-67 antibody (Porschen et al, 1991) and the MIB-1 antibody (Youssef et al, 1995) on oesophageal carcinomas. Thus, the mean Ki-67 index in the study of Porschen et al (1991) (35.7%) and the cut-off value to define low and high MIB-1 indices (mean or median were not given) in the study of Youssef et al (1995) (30%) are very close to the median (33%) found in our study.…”
Section: Materials and Methods Patientssupporting
confidence: 92%
“…The MIB-1 indices obtained in our study are in line with the results of earlier studies that had used the Ki-67 antibody (Porschen et al, 1991) and the MIB-1 antibody (Youssef et al, 1995) on oesophageal carcinomas. Thus, the mean Ki-67 index in the study of Porschen et al (1991) (35.7%) and the cut-off value to define low and high MIB-1 indices (mean or median were not given) in the study of Youssef et al (1995) (30%) are very close to the median (33%) found in our study.…”
Section: Materials and Methods Patientssupporting
confidence: 92%
“…In both of these studies, using the PCNA antibody, the intestinal-type carcinomas also had a higher growth fraction than the diffuse-type carcinomas, although the difference did not reach statistical significance. Furthermore, it was shown that in experimentally induced colon carcinomas also, the undifferentiated tumours exhibited a statistically significant lower tumour cell proliferation than differentiated gland-building tumours (Gabbert et al, 1982 findings are in accordance with those of some other studies using Ki-67 (Yonemura et al, 1990a;b, 1991), a positive correlation between a high PI and pT category was also reported using Ki-67 (Kakeji et al, 1991) or PCNA (Mori et al, 1993;Yonemura et al, 1993), whereas Jain et al (1991) reported a higher tumour cell proliferation index in lower pT categories using PCNA. In our study a statistically significant correlation was found between tumour cell proliferation at the invasion front and the presence of blood or lymphatic vessel invasion, which has been shown in the same population of patients to be important prognostic factors in gastric carcinomas (Gabbert et al, 1991).…”
Section: Discussionsupporting
confidence: 69%
“…Concerning the correlation of tumour cell proliferation with clinicopathological parameters, contradictory results have been reported in gastric cancer using either Ki-67 (Yonemura et al, 1990a, b, 1991Kakeji et al, 1991;Porschen et al, 1991) or PCNA (Jain et al, 1991;Mori et al, 1993;Yonemura et al, 1993;Maeda et al, 1995). In the present study we were able to show a statistically significant correlation between tumour cell proliferation and histological tumour type according to the Lauren classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ki-67 immunoreactivity has been studied in several types of carcinoma, e.g. in breast carcinoma (Barnard et al, 1987;Gasparini et al, 1992;Locker et al, 1992), in bladder carcinoma (Fontana et al, 1992), in carcinoma of the prostate (Thompson et al, 1992) and in colon carcinoma (Porschen et al, 1991 Tissue preparation The breast specimens were laid on ice and frozen in liquid nitrogen within 45 min. Sections for Ki-67 labelling, were stored at -20°.…”
mentioning
confidence: 99%